HUBUNGAN KEMAMPUAN DAN MOTIVASI DENGAN KINERJA PEGAWAI DI BADAN KEPEGAWAIAN NEGARA PUSAT JAKARTA (STUDI KASUS DI DIREKTORAT KOMPENSASI APARATUR SIPIL NEGARA) - Hani Setiowati; Nina Widowati; Moch. Mustam (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Employee's performance is the foundation of an organization's performance. This study aimed to determine the relationship of employee's ability and employee's work motivation of to the employee's performance in the Directorate of Civil State Compensation in Central State Personnel Board Jakarta. Researchers use a type of explanatory research by distributing questionnaires to obtain data on the 21 respondents. Testing was performed using Spearman rank correlation analysis. The results showed that the hypothesis that there is a positive correlation between ability and motivation on employee performance, acceptable significantly with a correlation coefficient of each relationship is the relationship between the performance of employees with employee's ability is 0.826 and the relationship between the performance of employees with employee motivation is 0.440. The results showed a positive and significant relationship between ability and motivation on employee performance. It is meant to improve the performance of staff in the Directorate of Civil State Compensation Reform in Central Jakarta State Personnel Board can be done by providing an assessment of employee performance, technical training for capacity building, and special attention to employees with regard to the availability of the policy on employee welfare.